Student Leadership Training: A Workbook to Reinforce Effective Communication Skills - Taub, Diane (Rowman & Littlefield Publishers, 2002)
The practice of students demonstrating their care and helping each other to achieve their goals and dreams has a long historical tradition. According to Taub, communication skills are at the heart of the matter, particularly when dealing with troublesome, personal, and emotional issues. This workbook was designed to help professionals assist students in reinforcing basic communication skills required for most student peer support and/or leadership programs, as well as being applicable to a more general universe. A variety of user-friendly exercises, activities, useful facts and statistics, and a description of a successful Peer Support program are included. Will benefit teachers, facilitators, and students.